IMPLEMENTASI SISTEM PAKAR UNTUK MENDIAGNOSA KERUSAKAN MESIN MOBIL TOYOTA AVANZA: Design, Expert System, Car Engine - Louis, Ahmad; Vinansia, Nopy (JURNAL AKADEMIKA, 2018)
Damage to the car engine occurs due to negligence in the maintenance. New car owners are aware of the damage after the car can not operate properly. Therefore in car use most likely require regular maintenance. By detecting damage to what happens to the car. For example, if the car sounds noisy and has no idea why it is happening, it is what drives the development of expert systems to identify car engine damage using Certainty Factor method. Submission of information was conducted using a Web-based site by requesting a request from the user. Request will be processed in the system then the results will be sent again to the user with displayed on the mobile device screen. It is expected that this system is able to provide optimal information from user and system feedback. This research is expected to provide information all matters relating to the problem of machine damage quickly and efficiently in lead both between user and system but still optimal even in small device